Improving The Use of Frans Kaisiepo Airport Through Alternative Election Development of Regional Potentials of Biak Numfor Regency (Case Study: Biak Numfor District, Papua) - Roviq, Muhammad Nur; Mauidzoh, Uyuunul; Poerwanto, Eko (Institut Teknologi Dirgantara Adisutjipto, 2019)
Frans Kaisiepo Airport is the airport with the first international status in the Papua region with the airport managing agency PT. Angkasa Pura I (Persero) and has runway specifications and airport facilities that are fairly good and complete. The airport is located in the Biak Numfor-Papua district, where the district has regional potential that can be developed to increase the utilization of the Frans Kaisiepo airport such as tourism, fisheries, industry and Biak Numfor as a place / space research facility. In this research, it is intended to choose alternative potential of the Biak Numfor district area to be developed in order to improve the utilization of the Frans Kaisiepo Biak Numforairport. In this study, the Analytical Hierarchy Process (AHP) method is used to choose the best alternative potential for the region from the existing potential areas, with the steps in the AHP are (1) Problem decomposition (2) Matrix preparation (3) Assessment /weighting for compare elements (4) Normalization (synstesis) of priorities and consistency tests and (5) Decision making / decision making. Then given suggestions for efforts to develop the potential of selected areas using SWOT analysis. The results of the priority assessment in this study, the final results for the selection of alternative potential areas that are expected to increase the use of Frans Kaisiepo airport are tourism potentials that have the highest priority weight of 0.379, followed by fisheries potential with a priority weight of 0.318. Next, the third and fourth priority sequentially are industry potential and space research facilities with a weight of 0.169 and 0.132. From the results of the SWOT analysis, several efforts that can be made to develop the tourism potential of Biak Numfor Regency are as follows: (1) Optimizing management of tourism potential (2) Increasing tourism promotion efforts in Biak Numfor district (3) Increasing professional human resources to improve the tourism performance of the Biak Numfor district area.